Desmos et philia chez Platon - Létitia Mouze (Astérion)
I propose to explore Plato’s political notion of “bond” (desmos) and to determine its relationship with philia (friendship) between citizens, a sine qua non condition of community, and which can be identified with what we call “the social link”. In this perspective, two texts are examined: The Laws, VII, 793a-d and The Statesman, 305e sqq.). Although the term desmos is examined in each of them from a different point of view (objectively in the Laws, where it designates the customs which streamline and strengthen the legislative edifice; subjectively in the Statesman, where it designates the true opinion present in souls, which enables them to harmonize their conceptions and therefore their actions), in fact desmos is formed each time by the common ways of doing things, which are based on common opinions. The fruit of education, an essential and primary political endeavor, the absence of desmos renders philia, that is, the social link, impossible, and therefore community equally impossible when understood as multiplicity unity of plurality.